Metaphor and Cognition - Hu, Zhuanglin. author. aut Link
XVII, 241 p. 16 illus., 1 illus. in color.
Keywords: This book collects virtually all research perspectives on metaphor in the field of cognitive linguistics. Moreover, it presents a comprehensive range of research methods for metaphor including qualitative and quantitative methods and the combination of the two. For example, critical metaphor analysis, metaphor interpretation, metaphor experiments, neuro method, and so on are all explained in detail.